2018
DOI: 10.3389/fpsyg.2018.00952
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parental Involvement and Socioeconomic Status on Junior School Students’ Academic Achievement and School Behavior in China

Abstract: A survey was conducted on 19,487 Chinese junior school students to elucidate the moderating role of socioeconomic status (SES) in the relationship between parental involvement (i.e., home-based involvement and academic socialization) and junior school students’ performance in school (i.e., academic achievement and school behavior). The data includes 10,042 males and 9,445 females (mean age = 14.52, SD = 1.24). It was taken from the 2013–2014 Chinese Educational Panel Survey (CEPS), that was administrated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 42 publications
7
43
1
1
Order By: Relevance
“…Lastly, Hoover-Dempsey and Sandler (1995,2005) explained that outside demands on parents' time can prevent them from engaging in their students' learning even when they understand their responsibilities and are motivated to fulfill them. As a result, providing a regular place and time to learn with an engaged facilitator is especially important for student populations where parental engagement has been persistently low, including students whose parents have limited formal education (Al-Matalka, 2014) and/or who have lower socioeconomic status (SES) (Alghazo & Alghazo, 2015). Furthermore, facilitators in this research found that students struggled to complete work at home when they had no or slow Internet access.…”
Section: Discussionmentioning
confidence: 89%
“…Lastly, Hoover-Dempsey and Sandler (1995,2005) explained that outside demands on parents' time can prevent them from engaging in their students' learning even when they understand their responsibilities and are motivated to fulfill them. As a result, providing a regular place and time to learn with an engaged facilitator is especially important for student populations where parental engagement has been persistently low, including students whose parents have limited formal education (Al-Matalka, 2014) and/or who have lower socioeconomic status (SES) (Alghazo & Alghazo, 2015). Furthermore, facilitators in this research found that students struggled to complete work at home when they had no or slow Internet access.…”
Section: Discussionmentioning
confidence: 89%
“…Test scores were standardized (mean [SD]: 0 [1]) by subtracting the mean of 70 from the original scores and dividing by an SD of 10; this is the most used method for standardizing test scores in the Chinese educational system. These standardized subject test scores are comparable across adolescents both within the same and across different academic years (19).…”
Section: Methodsmentioning
confidence: 97%
“…For standardized subject test scores, annual midterm exam scores for math, Chinese, and English in grades 7 to 9 were examined as outcome measures, which were abstracted from school administrative files by trained CEPS teams (19). These three subjects are regarded as foundational courses in the current Chinese educational system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that middle-class families’ expectations of educational success, which serve as an important means of class reproduction, shape their offspring’s aspirations to achieve success in their educational and career goals ( Devine, 2004 ). On the other hand, students from privileged families obtain more educational resources, and they tend to have higher academic achievement ( Bourdieu, 1986 ; Byun et al, 2012 ; Duan et al, 2018 ). It should be noted that educational resources particularly cultural capital, for middle-class students, is primarily accumulated within their families.…”
Section: Introductionmentioning
confidence: 99%